2013
DOI: 10.1007/s10493-013-9726-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative toxicity of pesticides in three phytoseiid mites with different life-style occurring in citrus: Euseius stipulatus, Neoseiulus californicus and Phytoseiulus persimilis

Abstract: Registro de acceso restringido Este recurso no está disponible en acceso abierto por política de la editorial. No obstante, se puede acceder al texto completo desde la Universitat Jaume I o si el usuario cuenta con suscripción. Registre d'accés restringit Aquest recurs no està disponible en accés obert per política de l'editorial. No obstant això, es pot accedir al text complet des de la Universitat Jaume I o si l'usuari compta amb subscripció. Restricted access item This item isn't open access because of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 31 publications
1
18
0
2
Order By: Relevance
“…Though abamectin is toxic or has sublethal effects on some phytoseiid species, it was reported as harmless for A. swirskii and only slightly harmful to E. stipulates , which is considered a rather tolerant species . Similarly, we did not detect an effect of abamectin application on the phytoseiids in Akko.…”
Section: Discussionmentioning
confidence: 67%
“…Though abamectin is toxic or has sublethal effects on some phytoseiid species, it was reported as harmless for A. swirskii and only slightly harmful to E. stipulates , which is considered a rather tolerant species . Similarly, we did not detect an effect of abamectin application on the phytoseiids in Akko.…”
Section: Discussionmentioning
confidence: 67%
“…This is surprising given that both active ingredients are in the same mode of action group (Group 10, mite growth inhibitors). Argolo et al . found that P. persimilis and N. californicus experienced moderate mortality (~38–48%) due to etoxazole, but did not report on other variables.…”
Section: Discussionmentioning
confidence: 99%
“…It has been used for controlling Panonychus citri, Raoiella indica, Tetranychus urticae and Tarsonemus pallidus , P. ulmi and Aculus schlechtendali . However, the use of pesticides can hamper the effectiveness of natural enemies, interfere with their physiology, behavior, and population growth, alter the balance between natural enemies and their prey, lead to ecological backlashes, and disrupt the ecosystem services they provide . Therefore, the conservation and augmentation of natural enemy insects in a pest management system mainly based on pesticides are important strategies to reduce the side effects of acaricides, while improving the efficiency of natural enemies.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have also shown that several predatory mites could be highly compatible with spirodiclofen; however, the adverse consequences that arthropod natural enemies are negatively affected by sublethal spirodiclofen concentrations in different ways, such as physiological events, mortality, longevity and reproduction, parasitism rate and emergence rate and life‐table parameters have also been reported. However, it is not understood comprehensively how spirodiclofen affects the development, survival, fecundity, and population growth of O. flavicornis , which is the primary consideration for the compatibility of natural enemy insects with pesticides.…”
Section: Introductionmentioning
confidence: 99%